Status Unsur - Unsur Basa (Ca2+ , Mg2+, K+, and Na+) di Lahan Kering Madura - Slamet Supriyadi (Agrovigor, 2009)
Objective of this research was to examine the content of  base cations (Ca2+ , Mg2+, K+, and Na+) in soil of dry land in Madura. The methode applied was survei research in four regencys. At every location 8 to 9 composite soil samples from 0 to 20 cm depth were taken. These samples were then air dried and sieved to pass 2mm diameter  for analysis of the cation content by means of  flamefotometer for K+, and Na+ and tetration method for Ca2+  and Mg2+.  Data were then analyzed based on the standart  content of cations in soil from  Pusat Penelitian Tanah (1993). Result showed that base saturation was high to very high class meaning the soil was rich in base cations, however the Ca/Mg/K ration was not ideal.  Exchangeable Ca was low to very high; exchangeble Mg was low to high. While exchangable monovalent cations were evry low to low. The low exchangable K was diadvantage as this cation was needed by plant in great number. Therefore, the main consideration in plant production was to keep the K concentration at certain level that was high enough to fullfill the plant need through fertilizer input. While low exchangable Na was advantages as this cation could create problem to disturb the physiology process in the plant and to reduce soil agregation when its concentration in soil was high.